Retroviral mediated gene transfer into bone marrow progenitor cells: use of beta-galactosidase as a selectable marker. - Strair, R K (1990)
Recombinant retroviruses have been utilized as vectors for gene transfer in model systems of gene therapy. Since many of these model systems require the transplantation of genetically modified primary cells it is important to devise methods which will allow the rapid and efficient selection for transplantation of only the cells which are capable of expressing high levels of the transferred gene. This report describes the use of beta-galactosidase as such a selectable marker. Bone marrow progenitors are infected with a recombinant retrovirus encoding beta-galactosidase. Using a fluorescence assay for beta-galactosidase we demonstrate that it is possible to use cell sorting to enrich for cells which will form bone marrow colonies that express high levels of beta-galactosidase. This rapid and non-toxic selection of bone marrow cells may facilitate attempts to achieve gene therapy in a variety of model systems.